Developing an online system to support algebra progress monitoring: Teacher use and feedback - Stecker, Pamela M.; Foegen, Anne (Frontiers in Education, 2022)
A brief overview of the development of an online system to support algebra progress monitoring across several years of an iterative process of development, feedback, and revision is provided. Online instructional modules addressed progress monitoring concepts and procedures; administration and scoring of three types of algebra measures, including teacher accuracy with scoring; and navigation and use of the online data management system, including data entry, graphing, and skills analyses. In the final year of this federally funded research project, a test of the functionality of the completed system as well as an evaluation of teachers’ knowledge, accuracy, and satisfaction with the online professional development was evaluated. Specifically, 29 general and special education secondary school teachers completed 11 fully developed online instructional modules independently and administered weekly two of three types of algebra measures across 10 weeks with one of their classes of students. Data analysis included teacher accuracy in the scoring of the measures; change in their knowledge of student progress monitoring and data-based decision making; and teacher satisfaction with the online system, including instructional content, feasibility, and usability for data-based decision making. Directions for future research and implications for classroom use of this online system are discussed.